Culturally Targeted Online Course Redesigns for English Composition and Research Writing: A Case Study - Hai-Jew, Shalin (My University, 2010)
The Enduring Legacies ReservationBased Project, now in its third year, supports Native American college students of a number of Pacific Northwest tribes. This paper addresses the pedagogical and elearning strategies applied to the culturally sensitive curricular redesigns for English Composition 1 and 2 (which involve essay writing and research writing respectively). These are foundational and required courses for a number of degree programs and certificates. The curricular redesigns for both courses address issues of cultural sensitivity, learner focus, and strategy, and apply concepts of universal design for more effective learning for a wide range of learners. With the redesigns now in place for a year for the EC1 course and one quarter for EC2, some early findings have emerged as well.
Keywords: Online course redesign; Cultural sensitivity; Enduring Legacies Reservation-Based Project; Evergreen State College; Washington Online (WAOL); Tribal Based Program; Grays Harbor College (GHC); Native American learners; English composition; Research writing